Plasma IL-10 Levels to Guide Antiviral Prophylaxis Prevention of Late-Onset Cytomegalovirus Disease, in High Risk Solid Kidney and Liver Transplant Recipients. Issue 1 (January 2016) - Limaye, Ajit P.; La Rosa, Corinna; Longmate, Jeff; Diamond, Don J.
Abstract : Background: Immune measurements that distinguish solid organ transplantation (SOT) recipients who control cytomegalovirus (CMV) infection from those who progress to CMV-disease (CMV-dz) may be clinically useful in guiding tailored prevention strategies. We previously reported that elevated plasma levels of the immune-modulator IL-10 are associated with late CMV-dz. Here we evaluate whether IL-10 levels measured soon after prophylaxis discontinuation are predictive of CMV-dz risk. Methods: Plasma IL-10 levels were quantitatively measured by ELISA kit in 40 D + /R − SOT patients. All 40 D + /R − high-risk patients were prospectively followed for at least 12 months post-SOT: 13 subjects developed CMV-dz, all within 6 months of prophylaxis discontinuation. Results: IL-10 was detectable at the first post-prophylaxis measurement for 11 of 13 subjects who developed CMV-dz. In contrast, IL-10 was detectable in only 6 of 27 CMV asymptomatic patients. Monitoring IL-10 plasma levels within 1 month prophylaxis suspension appeared to have clinically useful level of 85% sensitivity and 78% specificity. Conclusions: The exact role of IL-10 with its multiple immunoregulatory effects during CMV infection is not clear. Moreover, IL-10 production can be influenced by pathological and infectious contexts, and/or anti-rejection immunosuppressant therapy. Despite mechanisms of IL-10 dysregulation may substantially differ among SOT patients, our findings suggest that measurable plasma IL-10 soon after prophylaxis discontinuation may be an adequate indicator of subsequent CMV-dz. If a similar prognostic performance is confirmed in a larger D + /R − cohort, IL-10 plasma levels could be used to guide the length of prophylaxis, providing a clinically useful means to reduce the incidence of CMV-dz in high risk patients. Abstract : This study shows that measurable plasma IL-10 soon after prophylaxis discontinuation may be an adequate indicator of subsequent cytomegalovirus disease in solid organ transplant recipients with a sensitivity of 85% and a specificity 78%.